Thermal analysis of magnetic Iron-Oxide nanoparticle with combination of Water and Ethylene Glycol passes through a partially heated permeable square enclosure - Sumithra, A.; Kumar, B. Rushi; Sivaraj, R.; Öztop, Hakan Fehmi (Taylor & Francis Ltd, 2023)
The research explores the use of iron oxide nanoparticles to enhance the thermal properties of fluids like water and ethylene glycol. These nanoparticles find applications in engineering and medicine, including wastewater treatment and coatings. The study investigates magnetic nanoparticle movement in a permeable enclosure, considering heat, magnetic field, and electromagnetic effects. Using the MAC method, dimensionless equations were solved, and results were presented through graphs, charts, and tables. Findings show nanoparticle volume significantly impacts heat transfer in nanofluids compared to base fluids. Increasing nanoparticle volume from 0 to 0.05 improved nanofluid heat transfer by 0.278% and base fluid by 0.303%. Heat absorption and generation improved nanofluid transfer by 15.819% and base fluid by 0.596%. Nusselt number increased with higher Eckert number and heat source/sink parameters in both nanofluids and base fluids.
Keywords: Nanofluids; mixed convection; porous; viscous dissipation; heat source/sink; ohmic heating